2017
DOI: 10.1002/jhbp.444
|View full text |Cite
|
Sign up to set email alerts
|

Safety-related outcomes of the Japanese Society of Hepato-Biliary-Pancreatic Surgery board certification system for expert surgeons

Abstract: Background We investigated safety-related outcomes of hepatobiliary pancreatic (HBP) surgeries performed after establishment of the Japanese Society of HepatoBiliary-Pancreatic Surgery (JSHBPS) board certification system for expert surgeons. Methods We analyzed post-HBP surgery mortality data obtained from annual safety reports provided by board-certified training institutions between 2012 and 2015.Results The 90-day mortality rate for the 53,929 high-level HBP surgeries performed at board-certified training i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 22 publications
0
63
0
Order By: Relevance
“…However, the detailed analysis of recurrence pattern and the treatment for recurrence would not have been possible using population-based data [12,14]. In addition, although population-based analyses are said to better describe the outcomes achieved in routine practice [14], the trend in centralization of high-risk surgery is associated with improved shortas well as long-term outcomes [32][33][34][35][36][37][38][39][40][41][42]. Considering much better outcomes reported from high-volume liver centers [20,[43][44][45], the results demonstrated in the current study may reflect ideal practice in the near future when centralization is optimized for older patients with CRLMs undergoing hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the detailed analysis of recurrence pattern and the treatment for recurrence would not have been possible using population-based data [12,14]. In addition, although population-based analyses are said to better describe the outcomes achieved in routine practice [14], the trend in centralization of high-risk surgery is associated with improved shortas well as long-term outcomes [32][33][34][35][36][37][38][39][40][41][42]. Considering much better outcomes reported from high-volume liver centers [20,[43][44][45], the results demonstrated in the current study may reflect ideal practice in the near future when centralization is optimized for older patients with CRLMs undergoing hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This study used data from the registry of the Japanese Society of Gastroenterological Surgery and the Japanese Society of Hepato‐Biliary‐Pancreatic Surgery. The database is housed in the National Clinical Database, a platform for major nationwide registries in Japan.…”
Section: Methodsmentioning
confidence: 99%
“…However, the operative mortality and morbidity rates after HPB surgery are still high. Although the 90-day mortality rate after complex HPB surgery has been decreasing, it was reported to be 1.7% in Japan [2]. Furthermore, nationwide surveys in Japan revealed that postoperative morbidity rates after major hepatectomy and pancreaticoduodenectomy are 25.7 and 41.6% respectively [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Complex HPB surgery was defined according to the criteria of the Japanese Society of HepatoBiliary-Pancreatic Surgery [2]. The present study included 3 categories of procedures: hepatobiliary surgery, hepatopancreatic surgery, pancreatic surgery.…”
Section: Study Cohortmentioning
confidence: 99%
See 1 more Smart Citation